The protein, trypsin inhibitor and lipid of the winged bean [Psophocarpus tetragonolobus (L) DC] seeds - Khor, Hun‐Teik; Tan, Nget‐Hong; Wong, Kai‐Choo (Wiley, 1982)
The protein, trypsin inhibitor and lipid of the seeds from 15 New Guinea and 15 Thai winged bean varieties grown in Malaysia were analysed. The results show that winged bean seeds have a high protein content, ranging from 27.8 to 47.2% (based on dry seed wt). The trypsin inhibitor contents vary from 1.6 to 3.6 million i.u. 100 g−1 of seeds; these trypsin inhibitor activities could be destroyed almost completely by a simple heat treatment. The oil content varies from 15.2 to 27.8% of the dry seed wt. Saturated fatty acids account for 31–37% of the total fatty acids and behenic acid (22:0) alone constitutes about 14–17% of the saturated fatty acid content. Unsaturated fatty acids account for 63–69% of total fatty acids; oleic and linoleic acids together constitute 57–64% of the unsaturated fatty acids.